The Future(s) of the Mediterraneans: Between Uncertainty and Resilience - Carlo Capello; Panas Karampampas; Jutta Lauth Bacas (EtnoAntropologia, 2021)
In this introductory discussion, we argue that uncertainty can be seen as a common feature of Mediterranean countries beyond their varying histories and social realities. Such sense of uncertainty regarding the present and the future – strongly linked to economic instability and political turbulences – is analysed in this special issue through examples from the South and the North of the Mediterranean. A particular focus is laid on innovative forms of resilience, understood as actors’ capacities to adapt or deal successfully with change, or with challenging circumstances. However, we also discuss the limitations and potential misuses of the concept when applied uncritically. Equally important in the case studies presented here, in Greece as in Portugal, in Morocco and Tunisia as in the Italian case is the investigation of social actors’ perception of the future. Times of crisis and the capacity to aspire, anticipation and the individual or collective imagination: these are topics also investigated by the articles of this special issue, which are not only contributions to Mediterranean anthropology but also to the anthropology of the future. Altogether, the articles scrutinise how powerful imaginations of potential futures and orientations to the yet-to-come are in structuring individual and collective experience in times of political and economic uncertainty.